IN SILICO SCREENING FOR IDENTIFICATION OF NOVEL NON-PEPTIDIC FALCIPAIN 3 INHIBITORS BY VIRTUAL SCREENING, MOLECULAR DOCKING, AND MD SIMULATION - TRISHA RAJGURU; GOURI GOUTAM BORTHAKUR; PUNDARIKAKSHA DAS; MOUSUMI DAS GOSWAMI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The development of two new non-peptidic inhibitors against Falcipain 3 using computer-aided design. Methods: The researchers started by narrowing down a virtual library of compounds from the PubChem database to 800 drug-like compounds, which were then virtually screened and docked to identify the two most promising inhibitors. The screened compounds were then further studied using Molecular Dynamics Simulation. Results: The screened compounds were found to have potent antimalarial activity in silico. Conclusion: The proposed two lead compounds would serve as excellent targets for antimalarial drug. The efficacy of these potent inhibitors could be validated with laboratory experiments, with the goal of eventually developing an anti-malarial drug.